Abordagens de preparo e caracterização de nano-amidos e suas aplicações em emulsões alimentícias pickering: uma revisão - (:unkn) unknown (Universidade Federal do Amazonas, 2021)
Starch is one of the fundamental reserve compounds in plants. This low cost multifunctional biopolymer has been widely used in the food industry and in several industrial uses. In general, starches act as adhesives, binders and film-forming agents, in addition to acting as stabilizers providing creaminess, aiding in moisture retention and improving the clarity of paste, flavor, texture, shelf life and nutritional value of breads, cakes, cookies. The preparation and application of biodegradable nanoparticles has aroused interest in the research area and starch, being a naturally biodegradable polymer readily available in nature, is an excellent candidate for the formation of nanoparticles. Several methods are currently used to modify native starch into nano-starches in order to improve their technological properties and applicability in the food industry. Nano-starches are promising emulsion stabilizers. With Pickering's discovery, the possibility of using dispersed colloidal particles as emulsion stabilizers, known as “Pickering emulsions”, was observed. Where the solid particles adsorbed at the oil / water interface provide irreversible stability to the emulsions. The use of silica nanoparticles and other inorganic particles as stabilizers in the food and pharmaceutical industry has limited use due to concerns about biocompatibility and biodegradability. The current challenges are to standardize natural particles, such as starch, as biopolymers to stabilize emulsions in the food industry.
Keywords: Emulsões alimentícias; Biopolímero multifuncional; Indústria alimentícia; Nanopartículas biodegradáveis; Biocompatibilidade; CIÊNCIAS DA SAÚDE; Amido; Nano-amidos; Emulsões Pickering